2002
DOI: 10.1124/jpet.300.2.583
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of SC-57461A (3-[Methyl[3-[4-(phenylmethyl)phenoxy]propyl]amino]propanoic Acid HCl), a Potent and Selective Inhibitor of Leukotriene A4Hydrolase II: In Vivo Studies

Abstract: Leukotriene (LT) A 4 hydrolase is a dual function enzyme that is essential for the conversion of LTA 4 to LTB 4 and also possesses an aminopeptidase activity. phenoxy]propyl]amino]propanoic acid HCl) is a potent inhibitor of human recombinant LTA 4 hydrolase (epoxide hydrolase and aminopeptidase activities, K i values ϭ 23 and 27 nM, respectively) as well as calcium ionophore-induced LTB 4 production in human whole blood (IC 50 ϭ 49 nM). In the present study, we investigated its action in several animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…1h) demonstrates that this compound fills both arms, again suggesting it will impede PGP binding. It has previously been demonstrated that oral administration of SC57461A or a JNJ-40929837 derivative to naïve mice resulted in a potent inhibition of LTB 4 generation in an ex vivo whole blood assay2531. Importantly, we demonstrate that a comparable protocol, whereby SC57461A or JNJ-40929837 are orally administered to naïve mice, also potently abrogates serum aminopeptidase PGP-degrading activity (Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…1h) demonstrates that this compound fills both arms, again suggesting it will impede PGP binding. It has previously been demonstrated that oral administration of SC57461A or a JNJ-40929837 derivative to naïve mice resulted in a potent inhibition of LTB 4 generation in an ex vivo whole blood assay2531. Importantly, we demonstrate that a comparable protocol, whereby SC57461A or JNJ-40929837 are orally administered to naïve mice, also potently abrogates serum aminopeptidase PGP-degrading activity (Fig.…”
Section: Resultssupporting
confidence: 53%
“…It is feasible that the lack of success of these compounds may be due to their failure to distinguish between the opposing roles of LTA 4 H and thus inadvertently prevent PGP degradation. Searle/Pharmacia developed the potent, orally active inhibitor SC567461A that entered clinical trials for inflammatory bowel disease, but was withdrawn owing to adverse outcomes252627. DeCODE pharmaceuticals subsequently utilized a fragment based drug discovery program to identify inhibitors of LTA 4 H, leading to the development of the potent, orally active compound DG-051 that entered phase IIa clinical trials for myocardial infarction and stroke before further development being precluded282930.…”
mentioning
confidence: 99%
“…Inasmuch as LTA4H catalyzes the final and committed step in the biosynthesis of the potent chemotactic agent LTB 4 , this enzyme has been an interesting target for development of anti-inflammatory drugs. Thus, several highly potent and selective inhibitors have been developed within academia as well as industry (13)(14)(15)(16). However, none of these compounds have met the expectations and demonstrated clinical usefulness.…”
Section: Resultsmentioning
confidence: 99%
“…For SC57461A, dose-response studies were conducted using a range of doses surrounding 10 mg/kg (5, 10, and 20 mg/kg ip daily) based on equivalence of IC50 with zileuton and similar oral bioavailability (2). These studies demonstrated maximal inhibitory effect of SC57461A on lung LTB4 content at 10 mg/kg (data not shown), the same (orally administered) dose and dose interval reported to have inhibitory effects on inflammatory injury in adult rodents (22). Each litter was maintained at n ϭ 10 -12 pups to control for nutritional effects.…”
Section: Methodsmentioning
confidence: 99%